Analysis of the project success factor through time, cost, labour, health, safety, environment and quality aspects at PT XYZ - Moh Komarudin; Rosalendro Eddy Nugroho (International Journal of Production Management and Engineering)
This study aims to analyze the failure factors of PT. XYZ in 2018 – 2020 in terms of time, cost, labor, Health, Safety, and Environment (HSE), and quality based on the Success Project Factor (SPF). It includes 183 projects with the Non-Probability Sampling technique. The researcher uses fishbone and Pareto to identify problems. The results showed Schedule Performance Index (SPI)  1 indicated the project is in the late category, the Cost Performance Index (CPI)  1 indicated cost overrun, Safety Performance Index (SFPI)  0 indicated the K3 target could not be reached, the Client Satisfaction Index (CSI) = 34.03, indicated that it is in the dissatisfied category, then Productivity Coefficient Plan Realization, it meant the workforce was less productive. After the analysis of fishbone and Pareto, the data show that the highest cause was 13% due to lack of supervision, project cost aspects were 13% due to delays, HSE project aspect were 13% due to no K3 process before work begins, the quality aspect was 17% due to no training, and the labor aspect was 17% due to poor worker discipline.